1988
DOI: 10.1111/j.1600-0447.1988.tb06349.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenoceptor and imipramine receptor binding during the menstrual cycle

Abstract: The binding characteristics of platelet alpha 2-adrenoceptors, lymphocyte beta 2-adrenoceptors and platelet imipramine receptors were studied in five women during their menstrual cycle. A significant cyclic variation in the number of beta 2-adrenoceptor sites on intact lymphocytes was found during the menstrual cycle, while binding to alpha 2-adrenoceptors and imipramine receptors remained unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The lack of variation in [3H]imipramine binding during the menstrual cycle is consistent with an earlier pilot study on different subjects (Stowell et al, 1988) and the findings of Poirier et al (1986). The lack of correlation between sex steroid levels and [3H]imipramine binding parameters also suggests that physiological levels of these hormones in healthy women do not have a major influence on either imipramine receptor numbers or binding affinity, except perhaps during the post-partum period (Katona et al, 1984;Best et al, 1985).…”
Section: Discussionsupporting
confidence: 84%
“…The lack of variation in [3H]imipramine binding during the menstrual cycle is consistent with an earlier pilot study on different subjects (Stowell et al, 1988) and the findings of Poirier et al (1986). The lack of correlation between sex steroid levels and [3H]imipramine binding parameters also suggests that physiological levels of these hormones in healthy women do not have a major influence on either imipramine receptor numbers or binding affinity, except perhaps during the post-partum period (Katona et al, 1984;Best et al, 1985).…”
Section: Discussionsupporting
confidence: 84%
“…The sympathetic nervous system releases catecholamines into the synaptic cleft that may stimulate vasoconstrictive a2adrenoceptors and vasodilating j3,-adrenoceptors. Some investigators have found cyclical changes in platelet a,adrenoceptors [27], others found cyclical changes only in B,-receptors [28], and some no change at all [29]. Studies point to an influence of oestrogens on the sympathetic nervous system and there is evidence that oestrogens induce an up-regulation of (vasoconstrictive) a,-adrenoceptors [30-321.…”
Section: Discussionmentioning
confidence: 99%
“…However, this effect seems to be restricted to the use of a supraphysiological dose of the substance. Studies suggest an influence of estrogen on sympathetic nervous system, inducing cyclical changes in platelet adrenoceptors [19,20], modification in basal and stimulated norepinephrine excretion [21,22] and up-regulation of alphareceptors [23]. To date, there has been no well-controlled study on the vascular effects of estrogen in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%